Jual Beli Pakaian Bekas dalam Perspektif Fikih Muamalah Iqtishodiyah - Fauzi, Ahmad (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2019)
In the life of the world, Islamic law provides insight into economic policies. Many in everyday life people meet their lives by doing business. In economics, business is an organization that sells goods or services to consumers or other businesses for profit. This study aims to conduct an in-depth analysis related to buying and selling used clothing from the perspective of fiqh muamalah iqtishodiyah. This research is qualitative by using the documentation method in data collection. The conclusion of this research is that buying and selling used clothing does not violate the Sharia rules, but raises several negative aspects that need to be considered, namely aspects of health, cleanliness, and termination of employment in the clothing production industry.